Diffusional Kurtosis along the Corticospinal Tract in Adult Normal Pressure Hydrocephalus - Ades-Aron, B.; Yeager, S.; Miskin, N.; Fieremans, E.; George, A.; Golomb, J. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Normal Pressure Hydrocephalus is a reversible form of dementia characterized by enlarged ventricles, which can deform and cause disruptions to adjacent white matter fibers. The purpose of this work was to examine how diffusion and kurtosis parameters vary along the corticospinal tract and determine where along this path microstructure is compromised in patients diagnosed with normal pressure hydrocephalus. We hypothesized that disruption of the corticospinal tract from ventricular enlargement can be measured using diffusion MR imaging and this will be quantified in periventricular regions.MATERIALS AND METHODS: We developed a method to analyze diffusion parameters at discrete points along neural tracts. We then used diffusion MR imaging data from patients with Alzheimer disease and healthy controls to compare whether diffusion along the corticospinal tract differs from that of patients with normal pressure hydrocephalus.RESULTS: We found that diffusion parameters can differentiate patients with normal pressure hydrocephalus from those with Alzheimer disease and healthy controls: Axial diffusion, axial kurtosis, and the axonal water fraction were found to differ significantly across groups (P < .05) in an area located close to the superior internal capsule and corona radiata but below the cortex.CONCLUSIONS: A lower axonal water fraction indicates a lower axonal density in the corticospinal tract, which may indicate permanent damage. Lower axial kurtosis may imply that axons are being more aligned due to compression.ADaxial diffusivityAKaxial kurtosisAUCarea under the receiver operating characteristic curveAWFaxonal water fractionCSTcorticospinal tractFAfractional anisotropyNPHnormal pressure hydrocephalus